Formulation and standardization of lohasava: an ayurvedic aasava formulation Man - Tayde, Manisha A.; Ahire, Yogita G.; Mahale, Sunita N; Bhosale, Anuja P.; Patil, Sarika V. (Journal of Applied Pharmaceutical Research, 2024)
Background: Plant solutions or decoctions are fermented with added sugar to create alcoholic remedies like arishta and aasava. Standardizing ayurvedic formulations is essential to assessing the quality of medicine. Objective: Standardisation of Lohasava, which contains iron as a metal and is used as hematinic, has been carried out in the current study. Methods: The standard ayurvedic procedure was used to prepare the aasava formulation. Modern scientific control processes have standardized the formulation for the final products. Organoleptic analysis, phytochemical assessment, and physicochemical characteristics such as pH, specific gravity, viscosity, acid values, total solid content, alcohol content, heavy metal content, and stability studies were used to standardize asava. Additionally, formulations were examined for the presence of pesticides. Using UV-visible spectrophotometric analysis, the iron content was determined. Animal studies were carried out to evaluate pharmacological activity. Results: Physical and chemical parameters were found within limits. The alcohol content of formulations was within limits and indicated good fermentation. Conclusion: The study's findings have revealed good formulation quality and provide a standard for aasava and ayurvedic formulations.